PENGARUH LATIHAN BENCH PRESS TERHADAP KECEPATAN PUKULAN STRAIGHT PADA CABANG OLAHRAGA TINJU - Latuheru, Ricardo V.; Rizal, Andi (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2019)
This study aims to determine the effect of bench press exercises on the speed of straight punches in boxing. By using the field experiment method. The population used was boxing athletes in Makassar with a sample of 20 people taken by proportional random sampling from AMA Makassar club boxing athletes. The data analysis technique used is the t-test at 95% significance level. The results showed that; Bench press exercises have a significant effect on the speed of straight punches in boxing, proved t0 = 49,252> tt = 2,262.